Morality : the why and the what of it - Sterba, James P.; Gaus, Gerald (Westview Press, 2012)
An essential text for all students and scholars of ethics and political philosophy, this book offers a thought-provoking presentation of distinguished philosopher James P. Sterba's moral and political philosophy, with probing critical responses from some of the most prominent scholars in the field today.